Deoxidation of Titanium Using Ytterbium-Halide-Flux Method - Takanari OUCHI; Kenta AKAISHI; Gen KAMIMURA; Toru H. OKABE (Journal of MMIJ)
Efficient removal of oxygen (O) impurities from titanium (Ti) scrap is necessary to accelerate the recycling of Ti scrap. However, deoxidation of Ti is extremely difficult, both thermodynamically and technically. In this study, we developed a deoxidation technique that uses Yb (a rare earth metal with high vapor pressure at elevated temperatures) to directly remove O dissolved in solid Ti. Experimental results showed that deoxidation using Yb in halide salt fluxes such as LiCl and LiF produced Ti with O concentrations of 520-1400 mass ppm. The O concentration in deoxidized Ti samples was reduced to a level lower than that in Ti under the Yb/Yb2O3 equilibrium, probably owing to the decrease in the activity of Yb2O3, which was the deoxidation product, caused by its dissolution in the fluxes. In contrast, when vapor of Yb metal and halide salts were supplied to Ti samples via a gas phase, the Ti samples were deoxidized to the same O concentration as that under the Yb/Yb2O3 equilibrium. This deoxidation limit was controlled by the Yb/Yb2O3 equilibrium. The supply of halide salt vapor did not affect the deoxidation limit. The proposed deoxidation method is expected to help scale up the recycling of Ti scrap and ensure efficient utilization of resources.